Multimedia-Based Islamic Education Learning Patterns at SMK Muhammadiyah 8 Medan - Rizky, Nanda; Panggabean, Hadi Saputra; Tumiran, Tumiran (Riwayat: Educational Journal of History and Humanities, 2025)
Along with the rapid development of information technology, the use of multimedia in the learning process is expected to improve the effectiveness and interactivity of delivering Islamic Religious Education (PAI) materials. This study aims to analyze the learning patterns of multimedia-based Islamic Religious Education at SMK Muhammadiyah 8 Medan. The research employed a qualitative approach with a case study design, involving teachers and students as the research subjects. Data were collected through in-depth interviews, direct observation, and relevant documentation, and were analyzed using descriptive analysis techniques to provide a detailed description of multimedia application in PAI learning. The findings indicate that the use of multimedia in PAI learning not only enhances students' understanding of the material but also creates a more engaging and interactive learning atmosphere, in line with the needs of the digital generation. Furthermore, the role of the teacher as a facilitator becomes increasingly crucial in guiding students so that multimedia utilization remains oriented toward achieving learning objectives. This study implies that the integration of multimedia technology can serve as an effective strategy to improve the quality of PAI learning in vocational high schools